Pengembangan Suplemen Bahan Ajar Biokimia Dasar Materi Hormon Berbasis Kearifan Lokal Masyarakat Desa Pasti Jaya - Claudina Marditha; Masriani Masriani; Rini Muharini; Eny Enawaty; Ira Lestari (Jurnal Inovasi Pembelajaran Kimia (Journal Of Innovation in Chemistry Education), 2022)
The purpose of this study was to produce a supplement of basic biochemical teaching materials based on local wisdom of medicinal plants of the Pasti Jaya village community on appropriate hormone materials. The type of research used is Research and Development (R&D) which refers to research procedures according to Borg & Gall which have been simplified by the Center for Policy Research and Educational Innovation (Puslitjaknov) team, namely analyzing developed products, developing initial products, validating and revising, conducting small-scale field trials and revisions, as well as large-scale field trials and final products. Due to time constraints, the stages in this study were limited to the third stage, so that these stages were adjusted to the needs of the research. The resulting product was validated by 9 experts for each aspect of language, material, and graphics. The data collection technique used a feasibility validation questionnaire measurement technique which showed the validation results of all aspects with a very feasible category, respectively 96.3%, 95%, and 93.7% so that it was concluded that the supplement of basic biochemistry teaching materials based on local wisdom of the Pasti village community Jaya on the hormone material developed deserves to be tested in further research.